Design and Implementation of a Feasibility Trial to Promote Healthful Foods and Beverages at Baltimore City Food Pantries Using Policy, Systems and Environmental Strategies (P04-047-19). (13th June 2019) - Gunen, Bengucan; Yan, Sally; Adams, Lindsay; Ali, Shahmir; Poirier, Lisa; Gu, Yuxuan; Craig, Hope; Regan, Tim; Egan, Kathy; Gittelsohn, Joel
Abstract: Objectives: Ten % of low-income adults living in Baltimore reported using a food pantry in the last 30 days. Based on formative research in 22 Baltimore food pantries, most pantries stock a low variety of healthy foods and beverages, such as fresh fruits and vegetables, lean meats, low-fat dairy, and whole grains. To date, no intervention has attempted to improve the availability and accessibility of healthy options at food pantries in Baltimore, even though pantries are a consistent food source for low-income families in the city. Methods: The Maryland Food Bank's (MFB) Baltimore-based food pantries ( n  = 102) were classified as small, medium, or large based on the weight of food distributed annually. Out of eligible and interested pantries, 2 small, 2 medium, and 3 large pantries were selected. Intervention was delivered to 1 small, 1 medium and 1 large pantry in 3 8-week phases designed to address multiple levels of The Social-Ecological Model and key constructs of Social Cognitive Theory. Each phase focused on a different food group, based on formative research findings: lean & low-sodium proteins, fruits & vegetables, and healthy carbohydrates. Each phase included policy (stocking guidelines), systems (capacity-building training for pantry staff), and environmental strategies (shelf rearrangement; print materials, meal kits and cooking demos for clients). Intervention materials were developed in collaboration with MFB and food pantry staff, and included messaging from the Lerner Center's Kids Cook Monday campaign. Process evaluation measures were developed by the research team based on previous interventions at food retailers in Baltimore and included reach, dose delivered, and fidelity. Process evaluation data was collected at each weekly intervention visit. High standards were adjusted based on food pantry size. Results: Halfway through Phase 1, interventionists met, on average, 56% of high standards for reach, 78% of high standards for dose delivered, and 93% of high standards for dose delivered. The study team is revising its intervention delivery plans to improve reach and dose delivered. Conclusions: Policy, systems and environmental strategies promoting healthful foods are feasible to implement at food pantries of varying sizes in Baltimore; however, intervention delivery should be adjusted to fit food pantries' capacity and organizational goals. Funding Sources: Johns Hopkins University Lerner Center for Public Health Promotion, Johns Hopkins Urban Health Institute, Bloomberg American Health Initiative.